Forms of territorial organization recreational and tourist activities in the region - E. I. Nikolaeva (Kazimierz Wielki University, 2015)
The article analyzes the forms of territorial organization of recreational and tourist activities. The contribution of modern researchers to the development of tourist-tourist activity is considered. The interrelations between the various components that characterize the functional characteristics of each component of the recreational economy are considered, starting from the resources of the territory, including the stages of using the tourist product, until the end of the tourist tour.